Vocational training of young people and labor realities in a municipality of the Magdalena department - Viloria-Escobar, Javier
The objective of the research was to analyze the professional training of young people in a municipality in the department of Magdalena, taking as references the labor realities and the productive system. With a descriptive methodology and a population of 64 people, of which 37 are students currently, and 27 are already graduates, they were found as principal results that the area where they are formed are management science professionals and academics first destination is the Santa Marta city. Regarding graduates only 26% achieved the workforce linked in the municipality. In this sense, it is possible to conclude that there is a disconnect between vocational training of young people and the working reality of the municipality, which generates a slowdown in regional development and calls for effective intervention strategy.